The degree of mucosal atrophy is associated with post‐endoscopic submucosal dissection bleeding in early gastric cancer. Issue 5 (22nd February 2022) - Hayashi, Yoshito; Hatta, Waku; Tsuji, Yosuke; Yoshio, Toshiyuki; Yabuuchi, Yohei; Hoteya, Shu; Tsuji, Shigetsugu; Nagami, Yasuaki; Hikichi, Takuto; Kobayashi, Masakuni; Morita, Yoshinori; Sumiyoshi, Tetsuya; et al.
Abstract: Background and Aim: Despite the widespread use of endoscopic submucosal dissection (ESD) for early gastric cancer, post‐ESD bleeding remains a significant problem. Intragastric pH plays an important role in intragastric bleeding. Because gastric acid secretion contributes to intragastric pH, both the presence or absence of Helicobacter pylori infection and the degree of gastric mucosal atrophy may affect bleeding. The present study aimed to clarify the relationship between post‐ESD bleeding and the degree of gastric mucosal atrophy based on H. pylori infection status. Methods: We included 8170 patients who underwent ESD for early gastric cancer at 33 hospitals in Japan from November 2013 to October 2016. We analyzed the risk factors contributing to post‐ESD bleeding. Results: There were 3935 H. pylori ‐positive patients and 4235 H. pylori ‐negative patients. A nonsevere degree of gastric mucosal atrophy was an independent risk factor for post‐ESD bleeding in H. pylori ‐negative patients (odds ratio: 1.51, P  = 0.007), but not in H. pylori ‐positive patients (odds ratio: 0.91, P  = 0.600). Further, in H. pylori ‐negative, but not H. pylori ‐positive, patients, the rate of post‐ESD bleeding increased in a stepwise manner for patients continuing antithrombotic drug use, patients who withdrew antithrombotic drug use, and antithrombotic drug nonusers. Conclusions: Nonsevere gastric mucosal atrophy was a risk factor for post‐ESD bleeding in early gastric cancer in H. pylori ‐negative patients but not in H. pylori ‐positive patients.